MODEL KEPEMIMPINAN BERPIKIR SISTEM PRASEKOLAH ISLAM SWASTA - Awang Saputra; Agus Gunawan; Muhamad Fauzi (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2022)
The purpose of this paper is to explain the concept of systems thinking in the era of society 5.0 in the field of preschool education has a significant contribution and describes the thinking leadership of the private Islamic preschool level system. This research is qualitative research with a library research approach based on thematic in collecting data sourced from the internet, including books, journals and reports. Data analysis technique using content analysis. The system thinking concept is the way of thinking about the responsibilities organization with various problems and the need for solutions using systems thinking approach that is interrelated and affects. The educational leadership approach through classical, contextual, and identity studies that prioritize organizational leadership through planning, implementation, monitoring, and evaluation is appropriate for leaders for their leadership. The connection with education is that the leader of educational institutions must accumulate problems and their solution, of course, involves systems thinking. Levels of systems thinking can be applied at the preschool level with low levels of thinking, intermediate systems thinking, middle-high systems thinking, and high systems thinking. Islamic preschool education entirely teaches knowledge and understanding of the Islamic religion as the basis for the next level of education, experience, memorization, application, and future life. The Islamic education teaches systems thinking about the critical level to be trained as early as possible, the process of Islamic education becomes the primary curriculum in education.